Odpowiedzi

2010-01-06T17:33:53+01:00
7+(-2)=5
(-0,8)-(0,8)=0
7-(-2)=9
(-15)+(-3)=-18
-(¾)+(-¼)=-1
-(0,5)-(-½)=0
(-21)-(-15)=-6
-1,2-[-(-0,8)]=-2
24-(-15)+(-32)= 7
2010-01-06T17:35:47+01:00
7+(-2)=5
(-0,8)-(0,8)= - 1,6
7-(-2)= 9
(-15)+(-3)= -12
-(¾)+(-¼)= - 2/4
-(0,5)-(-½)= 0
(-21)-(-15)= 6
-1,2-[-(-0,8)]= - 2
24-(-15)+(-32)= 7
2010-01-06T17:35:53+01:00
7+(-2) = 7-2 = 5
(-0,8)-(0,8)=-0,8 - 0,8 = -1,6
7-(-2)=7+2= 9
(-15)+(-3)=-15 - 3 = -18
-(¾)+(-¼)=-¾-¼ = -1
-(0,5)-(-½) = -0,5- + ½= -0,5 + 0,5 = 0
(-21)-(-15)= -21 +15 = -6
-1,2-[-(-0,8)]= -1,2 + (-0,8)= -1,2-0,8 = -2
24-(-15)+(-32)= 24+15-32=39-32=7